pegegog 2021
DOI: 10.47750/pegegog.11.04.31
|View full text |Cite
|
Sign up to set email alerts
|

Quality improvement model of history education at university

Abstract: The implementation of history education at universities has not yet seen able to give optimal results. This study aims to propose a model for improving the quality of history education in higher education. It poses the primary research question: what is the quality improvement model of history education like according to the needs analysis? The research was conducted via a descriptive qualitative method. Data sources consisted of learning activities and documents related to the implementation of history educat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…This is based on the analysis results, which have found that the subject understands that positive integers are more significant than negative integers. Another factor that influenced the results of this study was the experience and habits often carried out by the subject, who tend to assume that positive integers are always greater than negative integers (Bofferding, 2014;Eko et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This is based on the analysis results, which have found that the subject understands that positive integers are more significant than negative integers. Another factor that influenced the results of this study was the experience and habits often carried out by the subject, who tend to assume that positive integers are always greater than negative integers (Bofferding, 2014;Eko et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Learning Indonesian history, which describes the collective events of a community or society is one aspect of the formation of a national personality (Adli & Fatimah, 2019;Pramono et al, 2021). Starting from a collective individual memory that leads to one goal, namely awareness of national identity through the history of the nation (Pramono et al, 2020;Fadli et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…History learning has the aim that all students are able to train their critical power to understand historical facts correctly and are based on a scientific approach and scientific methodology (Effendi, 2022;Pramono et al, 2021;C. B. Utomo & Wasino, 2020).…”
Section: Introductionmentioning
confidence: 99%